Assessing Fiscal Stress - Dobrescu, Gabriela (IMF Working Papers; Working Paper ;, 2011)
This paper develops a new index which provides early warning signals of fiscal sustainability problems for advanced and emerging economies. Unlike previous studies, the index assesses the determinants of fiscal stress periods, covering public debt default as well as near-default events. The fiscal stress index depends on a parsimonious set of fiscal indicators, aggregated using the approach proposed by Kaminsky, Lizondo and Reinhart (1998). The index is used to assess the build up of fiscal stress over time since the mid-1990s in advanced and emering economies. Fiscal stress has increased recently to record-high levels in advanced countries, reflecting raising solvency risks and financing needs. In emerging economies, risks are lower than in mature economies owing to sounder fiscal fundamentals, but fiscal stress remains higher than before the crisis.